The Analysis of the Determinant Factor of Premature Rupture of Membrane on the Inpartu Mother in the IRNA 1 RSU Moh. Noer Pamekasan - Lailatul Hafidah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Early Rupture of membranes is a rupture of the membranes when inpartu with opening at primipara less than 3 cm and in multiparas less than 5 cm, without depending on gestational age. Some factors which are suspected to be the cause of premature rupture of membranes are parity, history of KPD, sexual status and anemia. The purpose of this study is to analyze the determinant factor of premature rupture of membranes on the inpartu mother in the Inpatient Installation Room 1 RSU Moh. Noer Pamekasan. The type of research is quantitative research with cross sectional research design. The study was conducted on January 30 to March 15, 2018 in the Inpatient Installation Room 1 RSU Moh. Noer Pamekasan. The sample is 59 respondents taken with simple random sampling. The independent variables are parity, history of premature rupture of membranes, sexual status and anemia. Dependent variable is premature rupture of membranes. The data was analyzed by using logistic regression test with p = 0,05. The results showed that the variable X1 (parity) with p = 0.037; OR = 0,008, variable X2 (history of KPD) with p = 0,049; OR = 23.736), Variable X3 (sexual relationship status) with p = 0,064; OR = 19.770; Variable X4 (anemia) with p = 0,628; OR = 2,132. So it can be concluded that the factors which affect Y (the incidence of premature rupture of membranes) is a parity factor and history of KPD and the most dominant factor is the parity with the effect of 0.008.The high parity or parity of grandemultipara and the history of KPD to the previous labor affects the occurrence of premature rupture of membranes in the Inpatient Installation Room 1 RSU Moh.Noer. So it is necessary to do health education about the factors which affect the occurrence of premature rupture of membranes to prevent premature rupture of membranes recurring at the next labor